Auditory discrimination predicts linguistic outcome in Italian infants with and without familial risk for language learning impairment. (August 2016) - Cantiani, Chiara; Riva, Valentina; Piazza, Caterina; Bettoni, Roberta; Molteni, Massimo; Choudhury, Naseem; Marino, Cecilia; Benasich, April A.
Highlights: Italian infants with familial risk for LLI show deficits in RAP abilities. Early multi-feature RAP skills predict to later expressive language skills. Different acoustical features are critical to normative language acquisition. Early RAP skills represent a stable cross-linguistic risk marker for LLI. Early intervention programs should be implemented based on these results. Abstract: Infants' ability to discriminate between auditory stimuli presented in rapid succession and differing in fundamental frequency (Rapid Auditory Processing [RAP] abilities) has been shown to be anomalous in infants at familial risk for Language Learning Impairment (LLI) and to predict later language outcomes. This study represents the first attempt to investigate RAP in Italian infants at risk for LLI (FH+), examining two critical acoustic features: frequency and duration, both embedded in a rapidly-presented acoustic environment. RAP skills of 24 FH+ and 32 control (FH−) Italian 6-month-old infants were characterized via EEG/ERP using a multi-feature oddball paradigm. Outcome measures of expressive vocabulary were collected at 20 months. Group differences favoring FH− infants were identified: in FH+ infants, the latency of the N2* peak was delayed and the mean amplitude of the positive mismatch response was reduced, primarily for frequency discrimination and within the right hemisphere. Moreover, both EEG measures were correlated with language scores at 20 months. Results indicate that RAP abilities are atypical in Italian infants with a first-degree relative affected by LLI and that this impacts later linguistic skills. These findings provide a compelling cross-linguistic comparison with previous research on American infants, supporting the biological unity hypothesis of LLI.